Gratitude (Kebersyukuran) dan Psychological Well-Being Remaja Panti Asuhan Rahmatan Lil’alamiin - Frihapma Semita Ade; Irdam; Hafizatul Fitria Riyanda (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2022)
Living in an orphanage is a condition that is not expected by all teenagers, but there are some teenagers who have to live in an orphanage due to various factors. Life in an orphanage is also very complex with various problems that occur, especially for teenagers who enter the musical period and are still unstable. Psychological well-being with the gratitude (gratitude) they have is an important thing to see in adolescents. This study aims to determine the relationship between gratitude (gratitude) and psychological well-being in adolescents at the Rahmatan Lil' Alamin Orphanage, Padang City. The independent variable in this study is gratitude (gratitude) while the other variable is psychological well-being. The measuring instrument used in this study is a scale of gratitude (gratitude) and psychological well-being. The sampling technique in this study used a saturated sampling technique. The sample in this study was 60 teenagers at the Rahmatan Lil 'Alamin Orphanage, Padang City. Test the validity and reliability in this study using the Alpha Cronbach technique. The results of the validity coefficient on the gratitude scale move from rix = 0.479 to rix = 0.913 with a reliability coefficient of = 0.973 while the results of the validity coefficient on the psychological well-being scale move from rix = 0.349 to rix = 0.767 with a reliability coefficient = 0.926 . Based on data analysis, obtained a value of 0.629 with a significance level of 0.000 which means the hypothesis is accepted. Research shows that there is a significant relationship between gratitude (gratitude) and psychological well-being in adolescents at the Rahmatan Lil 'Alamin Orphanage, Padang City